Предмет: Математика,
автор: ItaTyan
(-16 - 13) в третей степени. * (- 2 27) - 542
Ответы
Автор ответа:
0
( - 1/6 - 1/3 )^3 = ( - 1/6 - 2/6 )^3 = ( - 3/6 )^3 = ( - 1/2 )^3 = ( - 1/8 )
( - 2 2/7 ) - 5/42 = - 2 12/42 - 5/42 = - 2 17/42 = - 101/42
- 1/8 • ( - 101/42 ) = 101/336 =
( - 2 2/7 ) - 5/42 = - 2 12/42 - 5/42 = - 2 17/42 = - 101/42
- 1/8 • ( - 101/42 ) = 101/336 =
Автор ответа:
0
Благодарю)
Похожие вопросы
Предмет: Українська мова,
автор: fr1zen2k19
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: erasylzaimolda
Предмет: Литература,
автор: ssaslulaDashappl8
Предмет: Математика,
автор: новенький6